Pengaplikasian Model Pelaksanaan Kuliah Kerja Nyata berbasis Kinerja dengan Program yang Adaptif di Masa New Normal - Besri Nasrul; Sri Endang Kornita; Chairul Chairul; Radith Mahatma; Hengki Firmanda; Geovani Meiwanda; Agrina Agrina; Zahtamal Zahtamal; Dahlan Tampubolon; Febrialismanto Febrialismanto; Indra Lesmana; Ibnu Daqiqil; Romi Kurniadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The purpose of implementing this community service is to apply a performance-based real work lecture implementation model with an adaptive program in the new normal period at the implementation of the Riau University Real Work Lecture (Kukerta). Implementation will be carried out in 2021 in all Kukerta locations for Riau University students in 2021. The focus of the model applied is the basis of indicators for assessing Kukerta implementation based on community service performance for universities. In addition, the programs that are prepared are also adaptive during the new normal. The results of the application show that there is a potential for increasing service performance outcomes through the implementation of this Kukerta, namely in the indicators (a) service with non-DRPM funding, (b) publication in the mass media, (c) partners with legal entities, and (d) books.